Центри “Західної групи” народного малярства на склі - Тріска, О. (Інститут народознавства НАН України, 2007)
The article suggests dividing the works of European folk painting on glass into three groups: western, central, and eastern ones. The Autor describes the centers of the „western“ group, in the majority of which folk painting on glass became established and developed with great intensity as a separate kind of folk art.